Risk assessment of irrigation-related soil salinization and sodification in mediterranean areas - Tomaz, Alexandra (2020)
UIDB/04683/2020 POCI-01-0145-FEDER-007690 ALT20-03-0145-FEDER-000004 UIDP/04035/2020